The comparison of bilateral trade between China and ASEAN, China and EU: from the aspect of trade structure, trade complementarity and structural gravity model of trade - Tang, Caihong; Rosland, Anitha; Li, Jie; Yasmeen, Rizwana (Routledge, 2024)
This article mainly compares China’s bilateral trade relation with the Association of Southeast Asian Nations (ASEAN) and with the European Union (EU), mainly from the perspective of China. We make the trade relation comparison in terms of trade volume and structure, trade complementarity index and impact factors on bilateral trade flow. We find the following results: (1) China mainly exports high-tech electronic and electrical and medium-tech products to ASEAN, and high-tech electronic and electrical and low-tech manufactures to EU yet imports high-tech electronic and electrical products from ASEAN and medium-tech products from EU. (2) China has strong competitiveness in low-tech manufactures and high-tech electronic and electrical area yet comparatively low competitiveness in medium-tech area; (3) China has high trade complementarity with EU in low-tech area and high trade complementarity with ASEAN in high-tech electronic and electrical area; (4) Based on structural gravity model of trade, the GDP per capita, monetary freedom, trade freedom and human development index have significant impacts on China-ASEAN and China-EU bilateral trade; WTO membership has impact on China’s trade with ASEAN yet not with EU; distance has impact on China’s trade with EU yet not with ASEAN.